Double low-dose computed tomography pulmonary angiography in the diagnosis of pulmonary embolism. (June 2019) - Aldosari, S; Al-Mantshari, A; AlQahtani, T; Almoudi, M; Al-Amary, A; Sun, Z
Abstract: The purpose of this study is to investigate the feasibility of double low-dose (low radiation and low contrast medium doses) computed tomography pulmonary angiography (CTPA) in the diagnosis of pulmonary embolism. This retrospective study involved analysis of 59 patients undergoing 64- and 128-slice CTPA examinations which were scanned with a pitch of 0.9 and 100 and 120 kVp, respectively, while flash mode of CTPA was done with a pitch of 3.2 and 120 kVp. There were no significant differences in image quality assessment between the low kVp and standard kVp or high-pitch CTPA protocols (p=0.181-0.186). The mean effective dose for the 100 kVp protocol was significantly lower than that for the120 kVp and the flash mode protocols (p < 0.001). The contrast medium was between 35-45 ml for the 100 and 120 kVp protocols, and 20-30 ml for the 120 kVp flash mode protocol. Double low-dose CT pulmonary angiography is feasible for detection of pulmonary embolism with acquisition of diagnostic images.